Linking the properties of accreting white dwarfs with the ionization state of their ambient medium. Issue 2 (5th May 2022) - Souropanis, D; Chiotellis, A; Boumis, P; Chatzikos, M; Akras, S; Piersanti, L; Ruiter, A J; Ferland, G J
ABSTRACT: Steadily accreting white dwarfs (WDs) are efficient sources of ionization and thus are able to create extended ionized nebulae in their vicinity. These nebulae represent ideal tools for the detection of accreting WDs, given that in most cases the source itself is faint. In this work, we combine radiation transfer simulations with known H- and He-accreting WD models, providing for the first time the ionization state and the emission-line spectra of the formed nebulae as a function of the WD mass, the accretion rate and the chemical composition of the accreted material. We find that the nebular optical line fluxes and radial extent vary strongly with the WD's accretion properties, peaking in systems with WD masses of 0.8–1.2 M_ . Projecting our results on so-called BPT diagnostic diagrams, we show that accreting WD nebulae possess characteristics distinct from those of H ii -like regions, while they have line ratios similar to those in galactic low-ionization emission-line regions. Finally, we compare our results with the relevant constraints imposed by the lack of ionized nebulae in the vicinity of supersoft X-ray sources (SSSs) and Type Ia supernova remnants – sources that are related to steadily accreting WDs. The large discrepancies uncovered by our comparison rule out any steadily accreting WD as a potential progenitor of the studied remnants and additionally require the ambient medium around the SSSs to be less dense than 0.2 cm^-3 . We discuss possible alternatives that could bridge the incompatibility between the theoretical expectations and relevant observations.